Horseradish—Armoracia rusticana Gaertn., Mey., Scherb. - James M. Stephens (EDIS)
This document provides an overview of horseradish cultivation, focusing on its characteristics, types, and propagation methods. It explains the differences between the common and Bohemian varieties, outlines the vegetative propagation process using root cuttings, and describes specific cultural practices aimed at producing high-quality roots. The document also notes that horseradish grows best in northern climates or high tropical elevations, as it does not thrive in Florida. Original publication date May 1994.